Encouraging Digital Innovation in Financial Recording: Analysis of the SIAPIK Application and the Will of MSME Entrepreneurs in the Shallot Farming Sector - Pramana, Andy Chandra; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (Universitas Kadiri, 2024)
This research aims to analyze the acceptance and willingness of shallot seed entrepreneurs to use the SIAPIK application in recording digital financial reports. The SIAPIK application, developed by Bank Indonesia, aims to help MSMEs manage their finances more efficiently and transparently. This research adopts a willingness to change model, which includes indicators of attitudes, subjective norms, behavioral control, intentions, and behavior. Data was collected through interviews with six shallot seed entrepreneurs who actively run their businesses. The results of the SWOT analysis of the SIAPIK application show strengths in ease of use and the trust given by Bank Indonesia, but there are weaknesses in terms of training needs for users who are less familiar with technology. Interviews with entrepreneurs revealed positive intentions and attitudes towards the use of digital applications, although there were concerns regarding technical capabilities and the need for further training. The results of this research show that the SIAPIK application has the potential to be adopted by shallot seed entrepreneurs if accompanied by adequate education and technical support, as well as taking into account the growing digitalization opportunities among MSMEs.